An Analysis of Africans’ Blind Worship Towards European Culture in V. S. Naipaul’s A Bend in the River - Cao, Dongdong; Jia, Xiao-yun (2021)
As an important early work of Nobel laureate Naipaul and a model of postcolonial works, A Bend in the River has been studied for decades. It is not hard to find Africans’ blind worship towards European culture after reading this book. This paper aims to explore the manifestations of Africans’ blind worship towards European culture in the novel by a close reading and acts as a wake-up call for almost every nations existing in the age of globalization to firm their own national cultural stand and enhance cultural confidence so as to remain invincible in the unprecedented changes.
Keywords: A bend in the river; Naipaul; blind worship of culture